2012
DOI: 10.1037/a0026809
|View full text |Cite
|
Sign up to set email alerts
|

Reliving emotional personal memories: Affective biases linked to personality and sex-related differences.

Abstract: Although available evidence suggests that the emotional valence and recollective properties of autobiographical memories (AMs) may be influenced by personality- and sex-related differences, overall these relationships remain poorly understood. The present study investigated these issues by comparing the effect of general personality traits (extraversion and neuroticism) and specific traits linked to emotion regulation (ER) strategies (reappraisal and suppression) on the retrieval of emotional AMs and on the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 96 publications
(130 reference statements)
6
48
0
4
Order By: Relevance
“…61 Other studies also demonstrated an association between personality traits and memory. 62 For example, Carlson and Levy 63 found an association between Extraversion and short-term memory, whereas Cuttler and Graf 64 reported a link between Conscientiousness and prospective memory. Memory, personality, behavior and academic performance are common areas of study for psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…61 Other studies also demonstrated an association between personality traits and memory. 62 For example, Carlson and Levy 63 found an association between Extraversion and short-term memory, whereas Cuttler and Graf 64 reported a link between Conscientiousness and prospective memory. Memory, personality, behavior and academic performance are common areas of study for psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that personality traits such as neuroticism and extraversion may induce opposing biases in the memory emotional information (Rusting, 1999;Denkova et al, 2012), and that sex-related differences in memory could be linked to dissociable engagement of emotion regulation strategies (Denkova et al, 2012), the neural circuitry mediating these effects remains poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…While factors associated with positive affect, such as extraversion (Costa & McCrae, 1980;John & Srivastava, 1999), are associated with positive memories (Rusting, 1999), personality traits associated with negative affect, such as neuroticism, are linked to negative memories (Mayo, 1983;Ruiz-Caballero & Bermudez, 1995). We recently identified such relationships in the case of retrieving personal memories for real-life events (Denkova et al, 2012). Namely, we showed that extraversion contributed to remembering more positive personal experiences and to maintaining a positive state, whereas neuroticism predicted the phenomenological characteristics of negative autobiographical memories; also, only the latter was modulated by sex-related differences.…”
Section: Personality-related Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…La MA opera con representaciones de episodios de vida, los recuerdos autobiográ-ficos (RsAs), los cuales posibilitan la reconstrucción, en el presente, de experiencias vitales previas. Los RsAs significativos, refieren a eventos de relevancia personal para los individuos (Denkova, Dolcos & Dolcos, 2012;Schaefer & Philippot, 2005). Así, se los ha caracterizado como recuerdos relativos a situaciones que marcan un antes y un después, experiencias de aprendizaje fuertemente vinculadas con la propia identidad o eventos que conforman hitos en el curso vital (Singer & Salovey, 1993;Sutin, Costa, Wethington & Eaton, 2010).…”
unclassified